Sensory impairments and subjective well-being status in middle-aged and older Chinese population: Cross-sectional and longitudinal analyses of a nationally representative survey - Zhou, Yifan; Lu, Yan; Liu, Ye; Hou, Yanan; Qian, Xinyi; Abuduxukuer, Kaiweisa; Xiang, Minhong; Peng, Qing; Luo, Jianfeng (Frontiers in Public Health, 2023)
Purpose: To investigate the impacts of sensory impairments (SIs) including single vision impairment (SVI), single hearing impairment (SHI) and dual sensory impairment (DSI) on subjective well-being measurements including life expectancy (LE), life satisfaction (LS) and self-rated health (SRH) in middle-aged and older Chinese population. Methods: We obtained data from the China Health and Retirement Longitudinal Survey (CHARLS). In total, 9,293 Chinese older adults aging over 45 were included at baseline 2011 in this study, and 3,932 participants who accomplished all 4 interviews from 2011 to 2018 were adapted for longitudinal analyses. Sensory status and subjective well-being measurements were collected. Other covariates included socio-demographic characteristics, medical condition and lifestyle-related factors. The impacts of baseline sensory status on LE, LS and SRH were assessed using univariate and multivariate logistic regression analyses. A linear regression analysis with generalized estimating equations (GEE) was used to assess the association between time-varying sensory statuses with LE, LS and SRH over 8 years after being adjusted with multi-confounding factors. Results: Participants with SIs had significantly lower level of LE, LS and SRH, compared to those who were free of SI. All kinds of SIs were significantly associated with LE, LS and SRH according to cross-sectional data. The correlations between SIs and LE or SRH over 8 years were also noticed. However, only SHI and DSI were found to be significantly associated with LS according to longitudinal data. (all p＜0.05) Conclusion: Sensory impairments had explicitly detrimental effects on both onset and progression in subjective well-being status over time among older Chinese population.